Dark matters on the surveillance of blackness - Browne, Simone 1973- (Duke University Press, 2015)
Notes on surveillance studies : through the door of no return -- "Everybody's got a little light under the sun" : the making of the book of Negroes -- Banding blackness : biometric technology and the surveillance of blackness -- "What did TSA find in Solange's fro'? : security theater at the airport -- Epilogue : when blackness enters the frame